Penguatan Kompetensi Perencana melalui Integrasi Evaluasi Pelatihan, Motivasi Kerja, dan Tata Kelola Birokrasi dalam Meningkatkan Kualitas Perencanaan Pembangunan - Susetyo, Ivan Budi (JURNAL ILMIAH GEMA PERENCANA, 2025)
The quality of development planning in Indonesia continues to face challenges, including the limited capacity of planning officials, the lack of synchronization among planning documents, and constraints in development data. This study aims to analyze how planner competence can be strengthened through the integration of functional training, work motivation, and bureaucratic governance. The article is based on empirical data from Pusbindiklatren Bappenas, findings from previous studies, and theories of competence, motivation, and governance. The results indicate that functional training for planners significantly enhances their knowledge, skills, and professional attitudes. Work motivation particularly the need for achievement and power also contributes positively to the improvement of planner quality. Moreover, the effectiveness of training is influenced by evaluation models based on the four levels of training evaluation and perceived training benefits, which together measure reactions, learning, behavior, results, and overall training benefits. Strengthened by the principles of good governance and a modern bureaucracy, the integration of these components provides a strategic foundation for improving the quality of development planning documents at both the national and regional levels.